2002
DOI: 10.1152/jn.00321.2002
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Depression: Imaging and Blockade in the Rat Neocortical Brain Slice

Abstract: . Spreading depression: imaging and blockade in the rat neocortical brain slice. J Neurophysiol 88: 2713-2725, 2002; 10.1152/jn.00321.2002. Spreading depression (SD) is a profound but transient depolarization of neurons and glia that migrates across the cortical and subcortical gray at 2-5 mm/min. Under normoxic conditions, SD occurs during migraine aura where it precedes migraine pain but does not damage tissue. During stroke and head trauma, however, SD can arise repeatedly near the site of injury and may pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(110 citation statements)
references
References 74 publications
9
99
0
Order By: Relevance
“…In line with previous in vitro (10,22,32) and in vivo (14) studies, we found that activation of the NMDA glutamate receptor is required for CSD, as demonstrated by the inhibition of CSD by the NMDA receptor antagonist L-APV. Conversely, CSD is not affected by blockade of the AMPA glutamate receptor.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with previous in vitro (10,22,32) and in vivo (14) studies, we found that activation of the NMDA glutamate receptor is required for CSD, as demonstrated by the inhibition of CSD by the NMDA receptor antagonist L-APV. Conversely, CSD is not affected by blockade of the AMPA glutamate receptor.…”
Section: Discussionsupporting
confidence: 92%
“…Clinical studies using neurophysiological approaches and imaging techniques have established a link between migraine aura and CSD. Auras most often anticipate headache onset, and experimental data indicate that CSD activates the trigeminovascular system, possibly provoking headache (5,10,12).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations